Technology-Enhanced Project-Based Learning for Developing Numeracy Skills in Elementary Education: A Systematic Literature Review - Dhina Cahya Rohim; Wardono Wardono; Noening Andrijati (Proceedings of International Conference on Science, Education, and Technology, 2026)
Numeracy skills are among the fundamental competencies that need to be developed in elementary school students. With the rapid advancement of digital technology, technology-enhanced Project-Based Learning (PjBL) has emerged as a promising instructional approach to support the development of these skills. This study aims to systematically review existing research on the implementation of technology-enhanced PjBL for developing numeracy skills in elementary education. The study employed a Systematic Literature Review (SLR) methodology following the PRISMA 2020 guidelines. A literature search was conducted in the Scopus database, yielding 623 records. After applying predefined inclusion and exclusion criteria, 23 articles were selected for further analysis. The findings indicate a growing research interest in technology-enhanced PjBL in recent years. The integration of technology within PjBL was found to positively influence students’ numeracy skills, conceptual understanding of mathematics, problem-solving abilities, critical thinking, and learning engagement. However, several challenges remain, including limited technological infrastructure, teachers’ digital competencies, and the management of project-based activities. In conclusion, technology-enhanced PjBL demonstrates significant potential for supporting the development of numeracy skills among elementary school students and warrants further exploration in both educational practice and future research.